1991
DOI: 10.2136/sssaj1991.03615995005500010011x
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Adsorption of Phosphate and Oxalate by Aluminum Oxides

Abstract: The aim of this work was to study: (i) the competitive adsorption of phosphate (P) and oxalate (OX) anions on an Al oxide as influenced by pH and order of anion addition; and (ii) the adsorption of P on and the desorption of OX from an Al precipitation product [Al(OH)x‐OX] formed in the presence of OX ions. The amount of P adsorbed on Al oxide in the absence of OX decreased with increasing pH. In the absence of P, OX adsorption exhibited a broad maximum between pH 5.0 and 7.0, but rapidly decreased at a pH <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
0
2

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(90 citation statements)
references
References 8 publications
7
81
0
2
Order By: Relevance
“…For the most part, the amount of DOC sorbed to the soils was similar between the dairy and poultry extracts and with little or no DOC sorption occurring with the swine effluent (Figure 3).The large amount of sorption of DOC in the dairy manure solution may explain why DRP sorption was much lower in this solution compared to the CaCl 2 and KCl solutions. Organic matter has been shown to reduce P sorption to soils by competing with P for sorption sites as well as complexing with metal oxyhydroxides (Bhatti, Comerford, and Johnston 1998;Ohno and Crannell 1996;Ohno and Erich 1997;Singh and Jones 1976;Violante, Colombo, and Buondonno 1991). On the other hand, studies have also reported increased P sorption due to the presence of organic matter (Guppy et al 2005a;Harter 1969;Redding, Shatte, and Bell 2006; Sanyal, De Datta, and Chan 1993).…”
Section: Phosphorus Sorption From Manurementioning
confidence: 99%
See 1 more Smart Citation
“…For the most part, the amount of DOC sorbed to the soils was similar between the dairy and poultry extracts and with little or no DOC sorption occurring with the swine effluent (Figure 3).The large amount of sorption of DOC in the dairy manure solution may explain why DRP sorption was much lower in this solution compared to the CaCl 2 and KCl solutions. Organic matter has been shown to reduce P sorption to soils by competing with P for sorption sites as well as complexing with metal oxyhydroxides (Bhatti, Comerford, and Johnston 1998;Ohno and Crannell 1996;Ohno and Erich 1997;Singh and Jones 1976;Violante, Colombo, and Buondonno 1991). On the other hand, studies have also reported increased P sorption due to the presence of organic matter (Guppy et al 2005a;Harter 1969;Redding, Shatte, and Bell 2006; Sanyal, De Datta, and Chan 1993).…”
Section: Phosphorus Sorption From Manurementioning
confidence: 99%
“…Following the 24-h sorption experiment, the pH of the manure solutions was significantly greater (P , 0.05) than that of the CaCl 2 for all eight soils and greater than the KCl solution for seven of the eight soils. Solution pH has been shown to be an important factor controlling P sorption to soils (Amarasiri and Olsen 1973;Barrow 1983;Traina et al 1986;Violante, Colombo, and Buondonno 1991). Solution pH determines the ratio of the different orthophosphate species, the charge at the soil surface, and the dominant soluble metallic-phosphate complex species (Berkheiser et al 1980).…”
Section: Phosphorus Sorption From Manurementioning
confidence: 99%
“…However, it is difficult to compare these results to those of adsorption in the absence of the committing anions for sorption sites because pH in the initial solution was changed such that increase in pH for oxalic acid and decrease in pH for phosphate. The effects of pH was observed by Violante et al (1991), showing that the increase in pH decreased the adsorption of phosphate and oxalic acid and vise versa. Therefore, the reduction in the adsorption of both anions on Chungwon Bt soil can be interpreted that both competition for common sorption sire by these anions and pH in solution influenced the adsorption of both anions in this study.…”
Section: Resultsmentioning
confidence: 99%
“…The reason may be related to the competition for adsorption among the P species. It has been proven that certain adsorption sites on metal hydroxide surfaces may favour orthophosphate while others may be specific for other phosphate species [31].…”
Section: Continuous Flow Testsmentioning
confidence: 99%